SOME FACTORS RELATED TO THE SEVERITY OF OBSTRUCTIVE SLEEP APNEA IN ELDERLY PATIENTS AT FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze several factors related to the severity of obstructive sleep apnea in elderly patients at Friendship Hospital.Patients and methods: A cross-sectional descriptive study was conducted on 46 elderly patients with obstructive sleep apnea who were examined and diagnosed at the Respiratory and Allergy Department, Friendship Hospital, from January 2023 to January 2025.Result: In the study group, 56.53% of elderly patients with obstructive sleep apnea had a normal BMI, and 41.3% had an overweight BMI. Neck circumference over 40 cm accounted for 95.65%, and 4.35% of patients had a neck circumference ≤ 40 cm. The average AHI was 8.77 ± 17.37, with 86.96% experiencing moderate to severe apnea. The two indices, AHI (severity of obstructive sleep apnea) and BMI, showed a strong positive linear correlation with r = 0.623 (p = 0.000 < 0.001); the regression equation was: AHI = 3.059 × BMI - 48.253. The two indices, AHI (severity of obstructive sleep apnea) and neck circumference, showed a strong positive linear correlation with r = 0.825 (p = 0.000 < 0.001); the regression equation was: AHI = 11.259 × Neck circumference - 442.824. There was a significant difference in the mean severity of obstructive sleep apnea with the Mallampati scale.Consclusion: Neck circumference and BMI showed a strong positive linear correlation with the severity (AHI) of obstructive sleep apnea. The higher the Mallampati score, the more severe the patient may have obstructive sleep apnea.
Keywords: Obstructive sleep apnea, neck circumference, BMI.